2017
DOI: 10.1371/journal.pone.0172274
|View full text |Cite
|
Sign up to set email alerts
|

The construct of sexual openness for females in steady intimate relationships

Abstract: The analysis of open-minded attitudes towards sexuality in general requires a construct based on attitudinal dimensions. Although several existing studies involve sexual attitudes, they differ substantially and standardized conceptual work is missing. Thus, the authors introduce the latent variable sexual openness to develop a construct based on self-oriented attitudes towards different sexual topics. Available survey data of female German students in a steady relationship allowed providing a first empirical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
3
0
1
Order By: Relevance
“…Particularly, several studies highlighted their impact in terms of prevention of sexually transmitted infections (McFarlane et al, 2002), sexual compulsivity (Delmonico and Miller, 2003) and violent sexual conduct (Mitchell, Finkelhor, & Wolak, 2007). Moreover, research showed that attitudes towards sexual behaviour have an important role in determining sexual well-being, as well as tolerance towards others' sexual behaviour (Atli Özbaş et al, 2016;Duyan and Duyan, 2005;Fino et al, 2017;Montesi et al, 2013;Rausch et al, 2017).…”
mentioning
confidence: 99%
“…Particularly, several studies highlighted their impact in terms of prevention of sexually transmitted infections (McFarlane et al, 2002), sexual compulsivity (Delmonico and Miller, 2003) and violent sexual conduct (Mitchell, Finkelhor, & Wolak, 2007). Moreover, research showed that attitudes towards sexual behaviour have an important role in determining sexual well-being, as well as tolerance towards others' sexual behaviour (Atli Özbaş et al, 2016;Duyan and Duyan, 2005;Fino et al, 2017;Montesi et al, 2013;Rausch et al, 2017).…”
mentioning
confidence: 99%
“…The observation of some pedigree-based studies that male and female homosexuals exhibit different segregation patterns, with males usually having more gay brothers than gay sisters, while lesbians, on the contrary, having more gay sisters than gay brothers, seems to suggest that the factors responsible for this familial aggregation are, at least partially, distinct in men compared to women ( Eckert et al, 1986 ; Jannini et al, 2010 ; Burri et al, 2011 ; Jannini et al, 2015 ; Bailey et al, 2016 ; Bogaert and Skorska, 2020 ; Diamond, 2021 ). Moreover, male sexuality tends to be bimodally distributed (heterosexuals versus homosexuals), whilst female sexuality exhibits a more continuous distribution with lower rates of homosexuality, and higher rates of bisexuality and “sexual openness” ( Rausch et al, 2017 ; Diamond, 2021 ). In other words, women are more likely to report a bisexual than an exclusively same-sex sexual orientation/attraction, with men showing, instead, the opposite pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Men’s sexual orientations are closely linked to their pattern of sexual arousal to male versus female erotic stimuli, which is not necessarily true among women. Furthermore, female sexuality tends to less temporal stability with respect to male sexuality: women appear more likely than men to experience same-sex sexual attraction in the context of close affectionate relationships, and their patterns of sexual attraction/orientation appear more likely to exhibit change over time, even though some studies have disconfirmed this ( Ott et al, 2011 ; Rausch et al, 2017 ). Of note, sex-/gender-specific aspects of human sexuality could also depend on the historically subordinate status of women, which “has made it more socially and economically risky for them to completely desist from heterosexual behavior, compared to men” ( Diamond, 2021 ), as well as on the “hegemonic notions of rigid masculinity” ( Diamond, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Los trabajos antecedentes han mostrado que la experiencia personal con la masturbación depende del tipo de actitudes construidas hacia este comportamiento sexual (Ortega et al, 2005), ante el cual es común el surgimiento de sentimientos de culpa y de una sensación de ansiedad (Watson & McKee, 2013), muchas veces determinado por el efecto de consideraciones externas como la valoración social o el impacto del juicio moral de su conducta íntima (Abdullah et al, 2018); al final de cuentas, las actitudes son un producto sociocultural. Experimentar tales sensaciones puede implicar la falta de aceptación de la propia sexualidad (Rausch et al, 2017), al igual que una visión más restrictiva de esta, permeada por emociones negativas.…”
Section: Iscusiónunclassified